Patterns of initial opioid prescribing and its association with short and long-term use among opioid naïve patients: Experience from Malaysia - Zin, Che Suraya; Nazar, Nor Ilyani; Rahman, N.; Ahmad, W.; Rani, Nurul Sahida; Kim Swan, Ng (2018)
Background and objective In the last decade, the use of opioids for chronic non-cancer pain (CNCP) conditions has increased significantly but it is not clear to what extent the increase reflects short-term use and to what extent it is caused by long-term use. Short-term use of opioids for acute pain conditions is considered appropriate, whereas the long-term use for CNCP (opioid prescribing of 90 days or longer) is always associated with much controversial due to lack of evidence supporting the long-term effectiveness of opioids in CNCP. In opioid naïve patients, the appropriate initial dose and duration of opioid use is suggested without inadvertently promoting the long term use while maintaining the desired effect of pain relief. This study examined the patterns of prescription opioid initiation and its association with short-term or long-term use among opioid-naïve patients.